Characteristics and driving mechanisms of mixing and stratification in Suances estuary using the potential energy anomaly budget equation - Lupiola, Jagoba; Bárcena, Javier F.; García-Alba, Javier; García, Andrés (Frontiers in Marine Science, 2025)
The environmental variability of rivers and tides create complex mixing patterns, which modulate the estuarine ecosystem services. Therefore, a thorough understanding of these systems is vital, not only for their protection but also for their recovery. This study first applies a method to analyze the different mechanisms driving the mixing and stratification of the water column in Suances estuary, a small estuary with large intertidal zones, by using numerical modeling to calculate the potential energy anomaly (ϕ) and its derivative (ϕt). Numerical results show that Suances estuary presents an ellipse of mixing and stratification variability driven by, firstly, the river flow (seasonal cycle – monthly time scale), secondly, the tidal phase (ebb-flood cycle – diurnal time scale) and, lastly, the tidal magnitude (spring-neap cycle – fortnightly time scale). Furthermore, these results explicitly highlight how the driving mechanisms can vary for the same estuary geometry at different locations due to diurnal, fortnightly and seasonal changes in forcing. The predominant driving mechanisms in Suances estuary are straining (S) tending to stratify the estuary, river and tide advection (A) tending to mix it and non-linear straining (N), caused by contributions from intertidal areas that favor mixing or stratification according to the tidal cycles. Additionally, a threshold was found between the potential energy anomaly and the depth of the water column, confirming that there are limiting values of the potential energy anomaly depending on the depth that can develop in the estuary. This is especially significant in small and shallow estuaries, since maximum values of the potential energy anomaly will be obtained as a function of depth.